Influence Of Leadership Style And Work Motivation To Employee Job Satisfaction (Case study on PT Indofood) - Tri cicik Wijayanti; Jamal Abdul Nasir; Sugeng Mulyono (International Journal of Economic Research and Financial Accounting, 2023)
The purpose of this study was to determine and analyze the influence of style leadership and work motivationagainst job satisfaction of employees at PT Indofood. This study was conducted by simple random sampling techniques (techniques simple sample), with a sample of 75 respondents. Whole regression equation the doubles used have met the requirements of the classical assumption test. Results of the study this shows that there is a significant and positive influence between the style leadership and motivation simultaneously to employee satisfaction in PT Indofood.